Episodic temporal structure modulates associative recognition processes: An MEG study. (20th March 2014) - Tibon, Roni; Vakil, Eli; Levy, Daniel A.; Goldstein, Abraham
Abstract The formation of mnemonic associations can occur between items processed in temporal proximity. It has been proposed that such intertemporal associations are not unitizable, and may therefore be retrieved only via recollective processes. To examine this claim, we conducted a magnetoencephalograph study of recognition memory for items encoded and retrieved sequentially. Participants studied successively presented pairs of object pictures, and subsequently made old‐new item judgments under several retrieval conditions, differing in degree of reinstatement of associative information. Correct recognition was accompanied by an early event‐related field (ERF) component, seemingly corresponding to the FN400 event‐related potential component asserted to reflect familiarity; this retrieval success effect was not modulated by degree of associative binding. A later ERF component, corresponding to the late positive component asserted to reflect recollection, was modulated by degree of associative reinstatement. These results suggest that memory of intertemporal associations, which are not amenable to unitization, is accessed via recollection.